Recovery of Ti and Zr metals from spent leaching solutions by a precipitation-reduction pathway. (February 2020) - Nersisyan, Hayk H.; Kwon, Suk Cheol; Re, Vladislav; Lee, Young Jun; Yoo, Bung Uk; Lee, Jong Hyeon
Graphical abstract: Highlights: Ba2 ZrF8 and BaTiF6 fluorides are precipitated from the spent liquors using BaF2 . The heating of Ba2 ZrF8 (BaTiF6 ) + Mg + k Cu mixtures yield a self-ignition at 600 °C. CuTi and CuZr alloy ingots and BaMgF4 slag are produced after the heating process. The chemistry of liquor purification and CuTi (CuZr) ingots formation is highlighted. Abstract: In this paper, we describe a progressive two-step process that allows titanium and zirconium fluorides (TiF4, ZrF4 ) contained in spent liquors of etched Ti and Zr alloys to be effectively recycled into CuTi and CuZr alloy compositions and a regenerated pickling acid of high purity. In the first step, spent pickling liquor is treated with a BaF2 suspension to produce water-insoluble BaTiF6 and Ba2 ZrF8 fluoride salts. In the second step, the as-precipitated BaTiF6 and Ba2 ZrF8 fluoride salts are mixed with Mg and Cu metals powder and heat-treated at 1300 °C to produce CuTi and CuZr alloy ingots. The microstructures of the ingots are discussed in regard to Cu concentration.